Contribution of Satellite Imagery, Geographic Information Systems, Pedology, and Statistical Analysis to the Characterization of Water Availability Potential in Urban Watersheds: Application to the Former Municipality of Ratoma (Republic of Guinea) - Tokpo Ninamou; Elegbede Manou Bernadin; Kourouma Mory; NTcha Tchantipe; Sine Diakite (European Scientific Journal, ESJ, 2025)
In response to the challenges associated with drinking water supply in urban areas, this study proposes an integrated approach to characterize the water availability potential of watersheds in the former municipality of Ratoma, Guinea. The research combines remote sensing (Shuttle Radar Topography Mission of USGS), Geographic information system (automatic extraction of watersheds and hydro-morphometric parameters), soil characterization, and multivariate statistical analysis. Based on the Digital terrain model, 38 watersheds were identified and described according to 29 hydro-morphometric parameters. Principal component analysis explained 86.24% of the total variance across three main axes: structural dimension (45.05%), the density of the hydrographic network (23.41%), and the energy of the relief (17.78%). Ascending hierarchical classification distinguished two functional groups: on the one hand, small basins (0.16-1.67 km²) with a rapid hydrological response, and on the other hand, larger basins (1.76-7 km²) with slower dynamics. At the same time, Ratoma's soil analysis identified nine soil units, dominated by skeletal formations (75%) with rapid drainage. Granulometric and qualitative analysis of the samples revealed significant textural variability that may influence infiltration. Coarse soils have a high infiltration capacity but low water retention, while fine soils exhibit temporary hydromorphy. Cross-referencing the results made it possible to spatially identify areas with high water potential (hydromorphic soils) and transit areas (skeletal soils), providing a valuable tool for decision-making in the sustainable management of groundwater resources in urban contexts, particularly for selecting sites suitable for drilling and for planning sustainable supply strategies.